The Effectiveness of Circular Hip Massage and Knee Press Massage toward Intensity Change of Labor Pain - Khoirunnisa', Fania Nurul; indrianingrum, Irawati; Tristanti, Ika (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Pain due to labor contraction will cause discomfort therefore pain management is needed to avoid negative effects on both mothers and fetuses. There are some methods in pain management. Pharmacological method has side effects meanwhile non-pharmacological method is more efficient and has minimal side effects. Massage is a non-pharmacological method which may overcome the pain of delivery (p <0.05). There is an easy method to use and support the delivery assistance for Mother’s Day Care, namely Circular Hip and Knee Press Massage. The aim of this study is to know the effectiveness of Circular Hip Massage and Knee Press Massage on the intensity of labor pain with the experimental quasi design. Thr research subjects were 52 pregnant mothers in March to July 2018 at the Maternity Home (RB) and Practice Midwives (BPM) in the Kudus Regency.. Based on the Wilcoxon test, the Circular Hip and Knee Press Massage methods are effective to overcome the pain of delivery (p <0.05). From Mann-Whitney Test can be concluded that there is a difference in the effectiveness of Circular Hip and Knee Press Massage on the Intensity change of labor Pain. The intensity change of labor Pain with Circular Hip Massage (CHM) is 0.9, median of 1 (SD 0.445). Meanwhile, the intensity change of labor Pain with Knee Press Massage (KPM) is 0.38, median of 0.5 (SD 0.697). The results of the study are expected to be a reference for the development of scientific health knowledge for mothers and children related to labor pain management.